Census of Public and Private Juvenile Detention, Correctional, and Shelter Facilities, 1990-1991: (United States) ([Verlag nicht ermittelbar], 1993)
These data provide information on the population and characteristics of public and private juvenile facilities in operation in the United States on February 15, 1991. Annual data for the 1990 calendar year are included as well. Questions designed to categorize each facility were asked concerning the number of adults held, the juvenile majority's custodial authority, reason for custody, and access to the community, as well as the facility's security arrangements, capacity, age, plans for renovation, type of administration, and setting. Extensive data on the total juvenile residential population of each facility was also gathered. The total population is broken down by admission type, legal status, type of offense, race, and age. The collection also contains information on the population's movement and average length of stay, as well as each facility's average daily population, personnel by race, number, and staff position, educational, treatment, and medical programs available, annual expenditures, court orders and consent decrees, and number of juvenile deaths that year.